World Wide Web Resources on Obstetrical and Gynecological Infections - Stavros Athanasiou; Eleni Pitsouni; Christos Iavazzo; Eirinaios M. Karamanis; Matthew E. Falagas (Hindawi Limited, 2007)
Modern information and communications technology has provided medical students and practitioners around the world with a new, valuable, and easy-to-use way to retrieve potentially useful information. Using previously described by our research group methodology, we generated a list of 50 Internet resources in the field of obstetrical and gynecological infections. We believe that the availability of such a list will help in the education of students and clinicians interested in obstetrical and gynecological infections.